KEPASTIAN HUKUM TENAGA KEFARMASIAN DALAM MENYELENGGARAKAN PELAYANAN KEFARMASIAN - Muhammad Ikhsan; Sabda Wahab (Jurnal MHKI, 2022)
Legal certainty for pharmaceutical staff is needed for legal protection, fulfillment of the rights of pharmaceutical workers and the fulfillment of patient rights in obtaining maximum pharmaceutical services. The purpose of this study was to determine the position and legal certainty of pharmacists in pharmaceutical services. This research is normative legal research with astatute approach with a qualitative research design. The results of the study indicate that pharmaceutical personnel have a position. The regulation of pharmaceutical services to date has not been in accordance with the principle of legal certainty. This is due to the finding of statutory provisions that allow health workers other than pharmaceutical personnel to provide pharmaceutical services, including: Article 35 paragraph (1) of Law no. 29 of 2004 concerning Medical Practice, Article 30 paragraph (1) letter j of Law no. 38 of 2014 concerning Nursing, Article 21 paragraph (1) PMK No. 9 of 2014 concerning Clinics and Article 1 of PMK No. 26 of 2020 concerning Amendments to the Regulation of the Minister of Health Number 74 of 2016 concerning Standards for Pharmaceutical Services at Health Centers.